J. Gołuchowski's Activity at Vilnius University - Rickevičiūtė, Kristina (Problemos, 1972)
The views of Józef Gołuchowski (1797–1858), a professor of Vilnius University, are revealed in the paper. Gołuchowski's lectures were very popular. They were attended not only by students but by inhabitants of the town as well. However, the tsarist authorities relieved Gołuchowski from his post of teacher of philosophy because of his materialistic ideas. It is difficult to say what the essence of his ideas was because no summaries of his lectures have reached our days. But Gołuchowski's books give us an evidence that he was an idealist, an adherent of the German classic philosophy, and that he took a great interest in Schelling's ideas. In his old age he deviated into mysticism.